Integrity in scientific research : creating an environment that promotes responsible conduct (National Academies Press, 2002)
"Integrity in Scientific Research attempts to define and describe those elements that enable and encourage individuals involved with scientific research to act with integrity. Providing a framework for research and educational institutions, this important book will be essential for anyone concerned about ethics in the scientific community."--Jacket